Cleopatra : a biography - Roller, Duane W. (Women in antiquity., 2010)
Few personalities from classical antiquity are more famous--yet more poorly understood--than Cleopatra VII, queen of Egypt. In the centuries since her death in 30 BC, she has been endlessly portrayed in the arts and popular culture, from Shakespearean tragedy to paintings, opera, and movies. Despite the queen's enduring celebrity, however, many have dismissed her as a mere seductress. In this major new biography, Duane Roller reveals that Cleopatra was in fact a learned and visionary leader whose overarching goal was always the preservation of her dynasty and kingdom. Roller's authoritative ac.